Design and Build Prototype of Field Soil Shear Test Equipment: Perancangan dan Pembuatan Prototipe Alat Uji Geser Tanah - Komarudin, Udin; Yanyan Agustian (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2025)
Shear strength analysis testing is a fundamental test in the field of civil engineering. The shear strength of the soil is greatly influenced by the parameters present in the soil, the higher the value of the obtained parameters, the higher the soil strength. To obtain these parameters, we need to conduct one of the soil shear strength tests. The soil shear test that has been conducted in the laboratory involves taking soil samples from the field, transporting them, and then conducting the tests. During the journey from the field to the laboratory, it is highly likely that the sample will undergo changes due to vibrations, shaking, or temperature. Some innovations that have been implemented weigh a maximum of 10kg, are portable and easy to carry, produce accurate test results, and are tested directly in the field. The design of the tool is made in a prototype before the assembly of the tool. The design of the direct shear test tool is made by referring to the standardized testing principles. After the device is assembled, a test is conducted on a soil sample using the standard procedure of the shear test apparatus.